Impact of presynaptic sympathetic imbalance in long-QT syndrome by positron emission tomography. Issue 4 (1st September 2017) - Zumhagen, Sven; Vrachimis, Alexis; Stegger, Lars; Kies, Peter; Wenning, Christian; Ernsting, Marko; Müller, Jovanca; Seebohm, Guiscard; Paul, Matthias; Schäfers, Klaus; Stallmeyer, Birgit; Schäfers, Michael; et al.
Abstract : Objective: We investigated the impact of cardiac presynaptic norepinephrine recycling in patients with long-QT syndrome (LQTS) using positron emission tomography (PET) with 11 C-meta-hydroxyephedrine ([ 11 C]mHED-PET). Methods: [ 11 C]mHED-PET was performed in 25 patients with LQTS (LQT1: n=14; LQT2: n=11) and 20 healthy controls and correlated with clinical parameters. [ 11 C]mHED-PET images were analysed for global and regional retention indices (RI) and washout rates (WO) reflecting dynamic parameters of the tracer activity. Results: Global and regional RI values were similar between patients with LQTS and controls. Although the global WO rates were similar between these groups, regional WO rates were on average higher in the lateral left ventricle (LV) wall in patients with LQTS (dose, mean ±SD; 0.08±0.14 vs 0.00%±0.09% min –1 ; p=0.033). In addition, patients with LQTS with a longer QTc interval showed a higher global WO rate. Clinical symptoms correlated with higher global WO rates. In the presence of normal global WO rates, asymptomatic LQTS patients showed higher global RI values. Conclusion: The increased regional WO rate of [ 11 C]mHED in the lateral LV suggests an imbalance of presynaptic catecholamine reuptake and release, resulting in a higher synaptic catecholamine concentration, in particular in LQT1 patients. This might enhance β-adrenoceptor signalling and thereby aggravate inherited ion channel dysfunction and may facilitate occurrence of ventricular tachyarrhythmias. Detection of regional differences in LV sympathetic nervous function may modify disease expression and potentially serve as a non-invasive risk marker in congenital LQTS. Trial registration number: 2006-002767-41;Results.